Sports coaching during the pandemic: Predicaments encountered by Filipino physical education teachers and potential strategies - Angoy, Raisalam; Ma'mun, Amung; Mahendra, Agus; Abduljabar, Bambang (Edu Sportivo: Indonesian Journal of Physical Education, 2024)
Background Problems: The educational disruptions and suspension of athletic competitions caused by the COVID-19 pandemic presented sports coaches with unique challenges in maintaining coaching and training activities for the athletes. Research Objectives: This study aimed to gain a comprehensive understanding of the experiences of physical education teachers who are also coaches in sports coaching amidst the COVID-19 pandemic. Methods: The study was qualitative, utilising a descriptive phenomenological design. Five participants willingly took part in an in-depth interview, ensuring the protection of informant data and maintaining anonymity. The instrument used was a semi-structured interview guide recorded via video and transcribed using Microsoft Word. Informed consent was obtained before the interview, and data analysis followed Collaizi's descriptive phenomenology for collecting, reducing, presenting, verifying, and concluding the data. Findings/Results: The findings of the study revealed several sports coaching predicaments: connectivity and communication issues, physical training conflict, administrative concerns, and psychosocial problems. Additionally, potential strategies were also revealed: connectivity and communication strategy, modified training method, administrative outsourcing initiative, and psychosocial initiative. Based on the results of the study, a proposed sports coaching intervention plan is highly recommended for utilisation to address several predicaments that emerged. Conclusion: Research shows that in grappling with pandemic-related challenges, coaches play a crucial role in maximising athletes' potential, necessitating a blend of skills and emotional resilience as they formulate effective coaching strategies for the predicaments encountered. Generally, this can contribute to more effective and well-rounded sports coaching, ultimately benefiting the athletes and the overall success of sports coaching and the school's sport-related programmes.